Diálogos com professoras que ensinam matemática em início de carreira - Kronbauer, Cíntia Fogliatto (2016)
This work is the product of an investigation that is part of the LP1: Research, Training, Knowledge and Professional Development Line of the Graduate Program in Education of the Federal University of Santa Maria / RS, focused on broadening the discussions in The initial training of teachers of mathematics and their first years of teaching. The aim of this research is to identify the constituent elements of the initial formation of teachers of mathematics that contribute to the first years of teaching, verifying the approximation and distances of the initial formation course and the reality experienced in the schools, through the gaze of the beginning teacher who teaches mathematics. The research theme came from the experience of the researcher as a teacher who teaches mathematics in her early years of teaching, given the emergence of problems, challenges, uncertainties and difficulties to be faced in the classroom, and that often the beginner teacher Is not prepared to face them. The theoretical references that base this writing that refer to the initial formation are Charlot (2000), Tardif (2002), Mizukami (2006), Imbérnon (2011), Vaillant; Garcia (2012), in the initial formation of teachers of mathematics are Ponte (1998), Moura (2001, 2002), Libâneo (2004), Lorenzato (2010), among others. In relation to the first years of teaching, the main references were Huberman (1992), Garcia (2009), Vaillant and Tardif (2002). For that, the investigation was carried out with teachers who teach mathematics in the state public network of the municipality of Ijuí / RS, the dialogue was recorded and occurred through semistructured interviews with seven teachers. Through their narratives we have been able to know them from the choice of the mathematics course, the first ones counted with the teaching in the initial formation and the entrance in the teaching career. With the transcribed dialogue the interpretation and understanding of the data was based on the narrative analysis of Galvão (2005) with the contribution of the hermeneutic experience, for understanding to happen, Gadamer (1997) argues that the interpreter moves from a projected meaning of the whole to the parts, and then returns to the whole, Called by the author of the hermeneutic circle, in this way the knowledge of the completeness of the text allows the interpreter to question between what is not familiar and what is being shared. The results allow us to share that the teachers understand that initial training is a necessary support for future practices, motivating and encouraging future teachers to think about mathematics teaching, however, during the training, there were difficult situations in the stages that marked The identity of these teachers. They concluded that the entry into the career was a moment of expectation but that feelings of insecurity, uncertainty, fears were greater and emphasized that the main deficiency in this initial period was in the organization of pedagogical practice and that the lack of support is Remarkable, end up resorting to experienced teachers. We conclude that the initial training course left some gaps strongly felt by the teachers at the beginning of the career, so they understand that the training course needs to provide more classroom practices, believe that they learn in practice, and could thus face with greater Clarity in classroom situations.